2011
DOI: 10.1021/jo201647b
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolidene Carboxylate Bound MBPh4 Complexes (M = Li, Na) and Their Relevance in Transcarboxylation Reactions

Abstract: Combination of 1,3-bis(2,6-diisopropylphenyl)imidazolum-2-carboxylate (IPrCO(2)) with the Lewis acids MBPh(4), where M = Li or Na, provided two separate complexes. The crystal structures of these complexes revealed that coordination to NaBPh(4) yielded a dimeric species, yet coordination of IPrCO(2) with LiBPh(4) yielded a monomeric species. Combination of 1,3-bis(2,4,6-trimethylphenyl)imidazolum-2-carboxylate (IMesCO(2)) with LiBPh(4) also afforded a dimeric species that was similar in global structure to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…Louie and coworkers have now shown that the strength of binding CO 2 to the NHC fragment is tunable in a series of decarboxylation and transcarboxylation studies [33,34]. Thermal stability studies have yielded a series of data shown in Fig.…”
Section: C1-carriers In Nature: Folate Chemistrymentioning
confidence: 99%
“…Louie and coworkers have now shown that the strength of binding CO 2 to the NHC fragment is tunable in a series of decarboxylation and transcarboxylation studies [33,34]. Thermal stability studies have yielded a series of data shown in Fig.…”
Section: C1-carriers In Nature: Folate Chemistrymentioning
confidence: 99%
“…Catalysts 2017, 7, 380 22 of 54 1,3-diaryl-imidazolium-2-carboxylates (78) have been used as CO2-transfer agents for the carboxylation of ketones and nitriles [66,106,111,112]. Reactions in which a "C-COO − " moiety behave as CO2-transfer agent towards an organic compound are not common.…”
Section: In Dmsomentioning
confidence: 99%
“…Carboxylated products are isolated in the form of metal salts in yield ranging from 60 to 81%. More recently Louie has undertaken a detailed mechanistic study on the abovementioned trans-carboxylation reaction by using IPr-CO2 (78), IMes-CO2 and I t But-CO2 as CO2-carriers [112]. Investigating the role played by the alkali metal, Louie succeeded in isolating NHC-CO2 .…”
Section: In Dmsomentioning
confidence: 99%
See 1 more Smart Citation
“…of acetophenone to form benzoyl acetate, or methanol to form monomethyl carbonate. [94][95][96] 1,3-Di-tert-butylimidazolium-2-carboxylate was used as recyclable organocatalyst in the cycloaddition of aziridines and carbon dioxide. 97 Imidazolium-2-thiocarboxylates were also described as organocatalysts.…”
Section: Scheme 36 Formation Of Isothiocyanate Adductsmentioning
confidence: 99%